2022
DOI: 10.1093/eurheartj/ehac544.1209
|View full text |Cite
|
Sign up to set email alerts
|

Absolute flow and resistance have a lower variability in repeated testing as compared to CFR and IMR: an EDIT-CMD substudy

Abstract: Background Invasive coronary function testing (CFT), including both acetylcholine (ACH) spasm provocation testing and assessment of coronary flow and resistance, is recommended to assess coronary vasomotor dysfunction (CVDys) in patients with angina and non-obstructive coronary artery disease (ANOCA). Objectives To determine repeat testing reliability of invasive measurements of CVDys. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar findings come from a recent study by Jansen et al in which 73 patients underwent baseline and follow-up CFTs after 6 weeks. In this study, the authors showed that continuous-derived Q and R at 6 weeks significantly correlated with their baseline measurements, while bolus-derived CFR and IMR values did not [78]. The variability of bolus-derived CFR between baseline and follow-up might be explained by different resting flow values between the first and the second measurement.…”
Section: Bolus Vs Continuous Thermodilution Methods To Assess Cmdmentioning
confidence: 58%
“…Similar findings come from a recent study by Jansen et al in which 73 patients underwent baseline and follow-up CFTs after 6 weeks. In this study, the authors showed that continuous-derived Q and R at 6 weeks significantly correlated with their baseline measurements, while bolus-derived CFR and IMR values did not [78]. The variability of bolus-derived CFR between baseline and follow-up might be explained by different resting flow values between the first and the second measurement.…”
Section: Bolus Vs Continuous Thermodilution Methods To Assess Cmdmentioning
confidence: 58%